Using CSR Theory to Examine Disaster Aid Response to the Wenchuan Earthquake. Issue 4 (May 2015) - Zhao, Ming; Wang, Fei; Zhao, Dingtao; Wei, Jiuchang
Abstract : What determines a company's response to a devastating calamity, whether near or far? A study of 454 publicly listed Chinese firms that contributed to relief efforts to aid the victims of the 2008 Wenchuan earthquake revealed that a variety of factors can influence the level of corporate disaster aid. These include the company's total assets, the degree of contact with customers, stakeholders' perceptions, media coverage, and even the length of time that top executives have occupied their position. These findings can guide business leaders in designing and implementing corporate social responsibility strategies that both deliver effective and compassionate assistance to those in need and are aligned with organizational resources and objectives. ©2015 Wiley Periodicals, Inc.